Acute effects of weighted baseball throwing programs on shoulder range of motion - Reinold, M. M.; Macrina, L. C.; Fleisig, G. S.; Drogosz, M.; Andrews, J. R. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Baseball pitching injuries are increasing at an alarming rate. While weighted ball throwing programs may be effective at increasing pitching velocity, previous research has identified a 24% injury rate and a 3.3° increase in shoulder external rotation (ER) range of motion (ROM) after performing a 6-week program. However, previous research has not investigated, separately, the immediate effects of throwing underloaded and overloaded balls on ROM. The purpose of this study was to examine the acute effects of throwing differently weighted baseballs on shoulder ROM. By analyzing these differences, it may be possible to determine the specific weight range that may lead to the greatest increase in ROM and potential injury risk.